1998
DOI: 10.1148/radiology.207.3.9609903
|View full text |Cite
|
Sign up to set email alerts
|

Chronic thyroiditis: diffuse uptake of FDG at PET.

Abstract: Diffuse thyroidal FDG uptake may be an indicator of chronic thyroiditis. The actual prevalence of the disorder was not low in this series, and such lesions may be found incidentally at FDG PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
81
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 0 publications
5
81
3
1
Order By: Relevance
“…Although diffuse thyroid uptake in FDG-PET is believed to be either a normal variant, chronic thyroiditis, or Graves disease, focal thyroid lesions have been associated with a high risk for malignant tumors. [1][2][3][4][5][6][7][8][9][10] Unfortunately, no definitive studies have identified specific characteristics that increase the likelihood of a malignant tumor. Although standard uptake values (SUV max ) has been introduced to predict malignant potential, investigators are still divided regarding this issue.…”
mentioning
confidence: 99%
“…Although diffuse thyroid uptake in FDG-PET is believed to be either a normal variant, chronic thyroiditis, or Graves disease, focal thyroid lesions have been associated with a high risk for malignant tumors. [1][2][3][4][5][6][7][8][9][10] Unfortunately, no definitive studies have identified specific characteristics that increase the likelihood of a malignant tumor. Although standard uptake values (SUV max ) has been introduced to predict malignant potential, investigators are still divided regarding this issue.…”
mentioning
confidence: 99%
“…A 1.8% prevalence of diffuse thyroid uptake was reported by Chen et al [9]. Yasuda et al demonstrated diffuse 18 F-FDG uptake in the thyroid in 36 of 1,102 healthy subjects (3.3%) [10]. These results showed relatively similar incidence of diffuse thyroid uptake in the healthy subjects and cancer patients.…”
Section: Discussionmentioning
confidence: 57%
“…In inflammatory conditions, the thyroid gland shows low attenuation on CT because of follicular cell destruction and loss of iodine concentration [14,18,19]. Thus, data regarding TgAb elevation, ultrasonography, and low attenuation value of CT revealed that chronic thyroiditis was suggested in 95.2% of the diffuse uptake group, and this percentage is similar to the 94.4% found by Yasuda et al [10]. Therefore, a possible explanation for diffuse uptake in the residual thyroid is mostly associated with chronic thyroiditis in the present study.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations